2022
DOI: 10.15406/ijh.2022.06.00299
|View full text |Cite
|
Sign up to set email alerts
|

Many oil wells, one evil: comprehensive assessment of toxic metals concentration, seasonal variation and human health risk in drinking water quality in areas surrounding crude oil exploration facilities in rivers state, Nigeria

Abstract: Background: Oil and natural gas extraction have produced environmental pollution at levels that affect reproductive health of indigenous populations. Accordingly, polluted drinking water from physical, chemical and heavy metals can result in serious health problems, like anemia, kidney failure, immunosuppression, neurological impairments, gastrointestinal as well as respiratory irritation, skeletal system abnormalities, liver inflammation, liver cancer, cardiovascular diseases after chronic exposure and other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(98 citation statements)
references
References 71 publications
7
89
2
Order By: Relevance
“…Surface water samples analyzed in this research were collected for twelve (12) months (June 2020 to May 2021) from three surface water bodies from different locations.…”
Section: The Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Surface water samples analyzed in this research were collected for twelve (12) months (June 2020 to May 2021) from three surface water bodies from different locations.…”
Section: The Study Areamentioning
confidence: 99%
“…Heavy-metal contamination of agricultural soils has become a significant environmental concern in human cultures, particularly in developing nations, at the same time as the growth and expansion of industry, mining operations, and excessive use of chemical fertilizers [25][26][27][28][29][30][31][32][33][34][35]. Studies have demonstrated that anthropogenic activities such as improper waste management [36][37], industrial, mining, agricultural, and domestic activities as well as geogenic processes like weathering of rock minerals, rainfall intensity, leaching, and local geology of the aquifer [1][2][3][4][5][6][7][8][9][10][11][12][13] are the major controls on groundwater quality. Groundwater was severely contaminated as a result of excessive and unsustainable groundwater extraction for drinking and irrigation, irrigation runoff, surface contaminants permeating the groundwater system, a high rate of evaporation, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Also, the contaminated streams become sources of danger to organisms including man that depend on them for survival. [6][7][8][9][10][11][12][13] Pesticide residues poisoning has been documented as a killer by so many: cases include the mysterious deaths of over 18 people in Ode Irele, in Ondo State, Nigeria that was attributed to pesticides poisoning by the WHO (Sahara Reporters, 2015) and the poisoning of children reported as a major health problem in Zhejiang, China. 14 The United Nations has also noted that an average of about 200,000 people die from the toxic exposure of pesticides per year across the world, calling for tougher global regulation of substances meant to control pests or weeds for plant cultivation.…”
Section: Introductionmentioning
confidence: 99%